2011
DOI: 10.1038/cmi.2011.37
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of peripheral CD4+CD25+Foxp3+ T regulatory cells in mice with STZ-induced diabetes

Abstract: Complications arising from abnormal immune responses are the major causes of mortality and morbidity in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…To further assess whether indirubin alters the suppressive function of CD4 + CD25 + Foxp3 + Treg cells in ITP mice, we thus compared the immunosuppressive effects of CD4 + CD25 + Treg cells sorted by bead separation from ITP mice treated with or without indirubin using an in vitro immunosuppressive assay [ 18 ]. Naive CD4 + CD25 - T cells were used as responder cells as described in the materials and methods.…”
Section: Resultsmentioning
confidence: 99%
“…To further assess whether indirubin alters the suppressive function of CD4 + CD25 + Foxp3 + Treg cells in ITP mice, we thus compared the immunosuppressive effects of CD4 + CD25 + Treg cells sorted by bead separation from ITP mice treated with or without indirubin using an in vitro immunosuppressive assay [ 18 ]. Naive CD4 + CD25 - T cells were used as responder cells as described in the materials and methods.…”
Section: Resultsmentioning
confidence: 99%
“…Tregs are essential for the regulation of excessive inflammatory responses in the body, but the population size and function of Tregs in hyperglycemia-induced inflammation is controversial. Some researchers have shown that the frequencies and functions of Tregs do not change or decrease in hyperglycemic NOD mice 27 28 , whereas STZ-induced hyperglycemia in mice leads to an increased Treg population from the thymus and enhanced generation of Tregs in the periphery 29 . In accordance with this previous report related to STZ-induced hyperglycemia, we showed that Tregs were significantly increased in the inflamed liver tissues and mesenteric lymph nodes from the diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of diabetogenic T cells appears to be associated with defective immunoregulation [5] . Numerical and functional deficiencies of CD4 + FoxP3 + T regulatory (Treg) cells have been demonstrated in T1D [6] , [7] . However, Treg cells do not account for the entire regulatory functions; another regulatory T cell subset, invariant natural killer T (iNKT) cells, has also been demonstrated to be involved in the pathophysiology of the disease.…”
mentioning
confidence: 99%